2011
DOI: 10.1007/s10686-011-9271-0
|View full text |Cite
|
Sign up to set email alerts
|

Solar magnetism eXplorer (SolmeX)

Abstract: The magnetic field plays a pivotal role in many fields of Astrophysics. This is especially true for the physics of the solar atmosphere. Measuring the magnetic field in the upper solar atmosphere is crucial to understand the nature of the underlying physical processes that drive the violent dynamics of the solar coronathat can also affect life on Earth.SolmeX, a fully equipped solar space observatory for remote-sensing observations, will provide the first comprehensive measurements of the strength and directio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 34 publications
(25 reference statements)
1
13
0
Order By: Relevance
“…A spectropolarimetric measurement using Zeeman magnetometry by Lin et al (2004) found a LOS coronal magnetic field at 1.1 R above an active region to have a flux density of about 4 G. This value is very much in line with many other estimates shown in Fig. 5 of Peter et al (2012), and we therefore do not expect the flux density to be more than at most two or three times the nominal values given by our coronal model, i.e., 10 G. We note, however, that the only way of reproducing the full range of measurements plus uncertainties found by SUMER/SOHO, is by increasing the flux to the values cited in the previous paragraph.…”
Section: The O 5+ Preferential Heating Preferential Acceleration Ansupporting
confidence: 84%
“…A spectropolarimetric measurement using Zeeman magnetometry by Lin et al (2004) found a LOS coronal magnetic field at 1.1 R above an active region to have a flux density of about 4 G. This value is very much in line with many other estimates shown in Fig. 5 of Peter et al (2012), and we therefore do not expect the flux density to be more than at most two or three times the nominal values given by our coronal model, i.e., 10 G. We note, however, that the only way of reproducing the full range of measurements plus uncertainties found by SUMER/SOHO, is by increasing the flux to the values cited in the previous paragraph.…”
Section: The O 5+ Preferential Heating Preferential Acceleration Ansupporting
confidence: 84%
“…The ratio Lβ/Lα is about 10 −3 as in Labrosse, Li, and Li (2006) at 3 R ⊙ but it is about 10 −1 instead of 10 −2 in Labrosse, Li, and Li (2006) for 1 R ⊙ . With the quiet-Sun (Allen) model, the Lβ/Lα ratio is lower than 10 −1 at 1 R ⊙ and 2 × 10 −3 at 2.5 R ⊙ , which means that polarization measurements in the Lβ line (Peter et al, 2012) will face serious difficulties because of the low signal-to-noise ratio. Third, as far as the Hα intensity is concerned, Figures 5 and 6 provide a useful information on the proper line emission (lower than the Lβ line by a factor eight).…”
Section: Discussionmentioning
confidence: 99%
“…Lyman alpha polarimeters have been proposed twice as strawman instruments for ESA missions, first for the COMPASS mission proposed in response to the call for the M2 slot (Fineschi et al 2007), later as part of the SOLMEX mission proposed in 2008 in response to ESAs M3 call (Peter et al 2012). It is obvious that -given the explorative character of such an instrument -a demonstration of the principle including the successful interpretation of the harvested data is mandatory.…”
Section: Clasp -Chromosheric Lyman-alpha Spectropolarimetermentioning
confidence: 99%